2012
DOI: 10.1002/ieam.1309
|View full text |Cite
|
Sign up to set email alerts
|

Revision of sediment quality triad indicators in Puget Sound (Washington, USA): I. a Sediment Chemistry Index and targets for mixtures of toxicants

Abstract: The Washington State Department of Ecology annually conducts sediment quality monitoring in Puget Sound as a component of the Puget Sound Ecosystem Monitoring Program. Sediment samples are analyzed to determine the concentrations of about 170 chemical and physical variables. A Sediment Chemistry Index (SCI) was derived using the State of Washington Sediment Management Standards to account for the presence and concentrations of mixtures of toxicants. Mean Sediment Quality Standard quotients (mSQSq) were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The comparison of mean concentrations of the these metals with the standards for fresh water sediments indicates that, except Zn, the mean concentrations of Cd, Cr, Cu, Ni, and Pb were higher than the standards for fresh water sediments [15, 16] while only the mean concentrations of Cd in marine sediments [17] were higher than the standards (Table 4). However, due to increased metals concentration in the sediments of Tembi River, the rise of concentrations of heavy metals, in comparison with guideline in sediments, is expected in future.…”
Section: Discussionmentioning
confidence: 97%
“…The comparison of mean concentrations of the these metals with the standards for fresh water sediments indicates that, except Zn, the mean concentrations of Cd, Cr, Cu, Ni, and Pb were higher than the standards for fresh water sediments [15, 16] while only the mean concentrations of Cd in marine sediments [17] were higher than the standards (Table 4). However, due to increased metals concentration in the sediments of Tembi River, the rise of concentrations of heavy metals, in comparison with guideline in sediments, is expected in future.…”
Section: Discussionmentioning
confidence: 97%
“…This is far above the result obtained in sediments of Calabar River (Nwineewii et al 2018). The average concentration of metals in the sediment for both seasons is lower than the freshwater sediment guideline (Burton 2002;Long et al 2013). The low values obtained in sediments at various zones of the sampling point can be attributed to river current which moves most of the dissolved metals that should have settled within the river bed.…”
Section: Resultsmentioning
confidence: 71%
“…The Sediment Chemistry Index values (which compare ratios of concentration to Sediment Quality Standards for 39 chemicals, a subset of which are metals) for the Hood Canal site, central Puget Sound sites, and one of the south Puget Sound sites are all very similar. The other south Puget Sound site, which is close to the industrial port of Tacoma, has considerably more variable and on average worse chemical index values, indicating higher exposure to chemicals at this site (Long et al, 2013;Partridge et al, 2018). Results from our study overall showed higher metal concentrations in shellfish at the 20 m south Puget Sound site (Carr Inlet), and in some cases high concentrations in shellfish at the central Puget Sound site (Point Wells).…”
Section: Spatial and Seasonal Variability In Shellfish Trace Metal Bimentioning
confidence: 99%